2017
DOI: 10.1039/c6cp04226k
|View full text |Cite
|
Sign up to set email alerts
|

Polaronic transport in iron phosphate glasses containing HfO2 and CeO2

Abstract: The electrical and dielectric properties of three series of glasses, xHfO-(40 - x)FeO-60PO, 0 ≤ x ≤ 8 mol%, xCeO-(40 - x)FeO-60PO, 0 ≤ x ≤ 8 mol%, and xHfO-(38 - x)FeO-2BO-60PO 2 ≤ x ≤ 6 mol%, have been investigated by impedance spectroscopy over a wide frequency and temperature range. As expected, these glasses exhibit polaronic conductivity which strongly depends on the fraction of ferrous ions, Fe/Fe. Following a detailed discussion on the DC conductivity, we use the MIGRATION concept to model their conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 49 publications
11
39
0
Order By: Relevance
“…Observed trends suggest that the dominant parameter for the polaronic transport in these glasses is Fe 2 O 3 content and not the addition of B 2 O 3 . Interestingly, the DC conductivity of binary 40Fe 2 O 3 -60P 2 O 5 mol.% glass without B 2 O 3 which we previously reported [30] lies precisely on the linear dependence of DC conductivity versus Fe 2 O 3 content of the present glass system, see the black symbol in Figure 2c. This further supports our conclusion that the polaronic transport in these glasses is controlled solely by the iron oxide content and hence, polaron number density.…”
Section: Conductivitysupporting
confidence: 84%
See 1 more Smart Citation
“…Observed trends suggest that the dominant parameter for the polaronic transport in these glasses is Fe 2 O 3 content and not the addition of B 2 O 3 . Interestingly, the DC conductivity of binary 40Fe 2 O 3 -60P 2 O 5 mol.% glass without B 2 O 3 which we previously reported [30] lies precisely on the linear dependence of DC conductivity versus Fe 2 O 3 content of the present glass system, see the black symbol in Figure 2c. This further supports our conclusion that the polaronic transport in these glasses is controlled solely by the iron oxide content and hence, polaron number density.…”
Section: Conductivitysupporting
confidence: 84%
“…Here, it should be noted that the polaron number density depends not only on the total amount of Fe 2 O 3, but also on the fraction of Fe 2+ and Fe 3+ ions. For the Fe 2+ /Fe tot ratio ≤ 0.5 the polaron number density is determined by the product of number density of the total iron ions and fraction of ferrous ions, whereas for Fe 2+ /Fe tot ratio > 0.5 it is determined as a product of the number density of the total iron ions and the fraction of ferric ions [3,4,30]. In the previous structural study of this glass system [24], it was shown that there is no significant variation in Fe 2+ /Fe tot ratio since the fraction of ferrous ions for selected glasses changes from 0.16 to 0.22.…”
Section: Conductivitymentioning
confidence: 99%
“…The dispersive behavior is more visible at lower frequencies and temperatures, and shifts to higher frequencies at higher temperatures. In general, conductivity dispersion is characteristic for ionic as well as polaronic glasses [53] and, hence, it is not connected to the type of charge carriers. Instead, it is closely related to the structural disorder, one property which is common to all glasses.…”
Section: Electrical Transportmentioning
confidence: 99%
“…The dc conductivity for all the glass‐nanocomposites under investigation is shown in Figure as a function of reciprocal temperature. Smooth variation of the dc conductivity with temperature is the characteristic of semiconducting behavior of the samples of small polaron hopping conduction . However, in the high and low temperatures, the activation energies (Table ) were computed from the slope of the graphs in the two range of temperature.…”
Section: Resultsmentioning
confidence: 99%